Adoption, reinvention and amendment of renewable portfolio standards in the American states. (20th January 2016) - Carley, Sanya; Nicholson-Crotty, Sean; Miller, Chris J.
Abstract: It has long been recognised that interstate diffusion of policy innovations is comprised of distinct decisions including adoption, reinvention and amendment. Interstate influences are an important driver of these diffusion processes, but studies to date have not investigated the degree to which external influences vary across these decisions. We theorise that geographical peers will have the largest impact in adoption decisions; that ideological peers are an important source of policy information when states make decisions about "reinventing" innovations adopted by others; and that internal factors will drive the decision by a state to amend a policy. We test these expectations for renewable portfolio standards in the American states between 1996 and 2009. Results suggest that state policymakers emulate peers in adoption or policy design choices, and that internal influences have a stronger influence on amendment decisions than do external influences. These findings further our understanding of policy diffusion and state-by-state relations.